Ocorrência de fungos e micotoxinas em milhos de diferentes regiões do Equador - Fracari, Juliana Copetti (2024)
Maize is one of the most widely produced cereals in the world, used mainly in animal and human feed, and is considered an important source of carbohydrates and amino acids. Due to climatic conditions and their composition, cereals are a frequent target for fungal infection, and these microorganisms or their metabolites can cause economic and health problems, as well as wastage due to the loss of corn quality. The aim of this study was to analyze the occurrence of fungi and mycotoxins in corn grown in different regions of Ecuador. Thirty samples of maize from the coast and sierra of Ecuador were evaluated, where 24 grains belonging to each sample were disinfected in a 0.4% sodium hypochlorite solution and then placed in Petri dishes containing Dicloran Glycerol 18% Agar (DG18) and incubated at 25 °C for 7 days. The fungal species were isolated and identified according to the classic protocols recommended by the International Commission on Food Mycology. Analysis of multi-toxins was carried out using liquid chromatography coupled with mass spectrometry (LC-MS/MS). The study revealed that 93.3% of the samples analyzed (28/30) showed fungal infection, mainly by the genera Fusarium and Aspergillus, potential producers of mycotoxins. Mycotoxins were present in 90% (27/30) of the samples evaluated. Five classes of mycotoxins were detected according to their predominance: fumonisins (66.6%), zearalenone (30%) and aflatoxins (16%), group B trichothecenes (13.3%) and ochratoxin (3.3%). As for the co-occurrence of mycotoxins, in one sample of Ecuadorian corn up to three classes of mycotoxins were detected, while in two other samples fumonisins, trichothecenes B and zearalenone were present, and in another the combination of aflatoxins, fumonisins and zearalenone. The results obtained provide important and unprecedented information on the mycological and mycotoxicological quality of Ecuadorian corn, compounds which represent a health hazard to consumers of corn-based products and the related chain.